Are ecological communities the seat of endosymbiont horizontal transfer and diversification? A case study with soil arthropod community. Issue 21 (16th October 2021) - Gupta, Manisha; Kaur, Rajbir; Gupta, Ankita; Raychoudhury, Rhitoban
Abstract: Maternally inherited endosymbionts of arthropods are one of the most abundant and diverse group of bacteria. These bacterial endosymbionts also show extensive horizontal transfer to taxonomically unrelated hosts and widespread recombination in their genomes. Such horizontal transfers can be enhanced when different arthropod hosts come in contact like in an ecological community. Higher rates of horizontal transfer can also increase the probability of recombination between endosymbionts, as they now share the same host cytoplasm. However, reports of community‐wide endosymbiont data are rare as most studies choose few host taxa and specific ecological interactions among the hosts. To better understand endosymbiont spread within host populations, we investigated the incidence, diversity, extent of horizontal transfer, and recombination of three endosymbionts ( Wolbachia, Cardinium, and Arsenophonus ) in a specific soil arthropod community. Wolbachia strains were characterized with MLST genes whereas 16 S rRNA gene was used for Cardinium and Arsenophonus . Among 3, 509 individual host arthropods, belonging to 390 morphospecies, 12.05% were infected with Wolbachia, 2.82% with Cardinium and 2.05% with Arsenophonus . Phylogenetic incongruence between host and endosymbiont indicated extensive horizontal transfer of endosymbionts within this community. Three cases of recombination between Wolbachia supergroups and eight incidences of within‐supergroup recombination were also found. Statistical tests of similarity indicated supergroup A Wolbachia and Cardinium show a pattern consistent with extensive horizontal transfer within the community but not for supergroup B Wolbachia and Arsenophonus . We highlight the importance of extensive community‐wide studies for a better understanding of the spread of endosymbionts across global arthropod communities. Abstract : This manuscript characterizes incidence, diversity, extent of horizontal transfer, and recombination of three different endosymbionts ( Wolbachia, Cardinium, and Arsenophonus ) in a soil arthropod community. We utilized multilocus strain typing system (MLST) for Wolbachia and 16S rRNA gene for Cardinium and Arsenophonus to answer whether endosymbionts are being transferred within an ecological community first and then spreading through different arthropod communities across the world.